Pengembangan Media Pembelajaran Interaktif Berbasis Game Educandy Pada Kurikulum Merdeka Untuk Sekolah Dasar - Larasati, Anisa Nurlaila; Asmarani, Ratih; Susilo, Claudya Zahrani (IJPSE Indonesian Journal of Primary Science Education, 2024)
This development research was conducted with the aim of evaluating the feasibility of the Educandy game-based learning media implemented in the Merdeka curriculum, with a focus on supporting students in developing attitudes as Pancasila learners, including religious, diversity, cooperation, independence, critical thinking, and creativity. This study was conducted due to the difference in students' interests between games and the learning process.The researcher developed the Educandy game-based learning media in the form of a web-based application, aiming to serve as an interactive learning media to enhance the learning enthusiasm of fourth-grade students at SDN Kepanjen 1, Jombang. The main objective of developing this learning media was to produce appropriate and suitable learning media according to the learning needs.The development process of the Educandy game-based learning media adopted the Research and Development (R&D) method by applying the ADDIE model. The ADDIE model consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results of media validation, material validation, and questionnaires given to the students indicated that the Educandy game-based interactive learning media achieved a percentage of 91.5% with a highly valid category and can be used without revisions. Furthermore, the implementation results of the media among students and teachers showed an average percentage of 93% with a highly interesting category.